Assessment of students’ coordination abilities for mastering complex spatiotemporal skills - Mironov, A.O.; Maltsev, D.V.; Kitin, E.A.; Solnyshkina, Yu.O. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to assess the coordination abilities of students of managerial specialties for mastering complex spatiotemporal skills using standardized testing tools. Methods and structure of the study. The study participants (83 first- and second-year students of managerial specialties) performed standardized tests of spatial coordination. The standard deviation, the reliability level of the tests, and the factor loadings were calculated. Results and conclusions. The factor structure of students’ coordination abilities was revealed; it includes the ability to orient in space and lateral agility, which explain 75.4% of the coordination abilities of students of managerial specialties.